Implementation of Islamic Communication in Learning at SMP Plus Ulul Ilmi Medan - Amiruddin Siahaan; Budi Budi; Zulkhairi Zulkhairi; Edy Rosadi; Sudirman Sudirman (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to see the extent of the implementation of Islamic communication at SMP Plus Ulul Ilmi Medan and the obstacles faced in the implementation process. The research method that the author uses is descriptive qualitative by collecting data through observation, interviews and documentation based on the required data. The results showed that: (1) the vision and mission and motto of the school became the basis for the implementation of Islamic communication in the school environment which refers to the teachings of the Prophet Muhammad SAW. (2) Theimplementation of Islamic communication in verbal and nonverbal learning that is implemented in speech and deeds. (3) there are two obstacles in the implementation of Islamic communication. These obstacles are caused by two factors, namely: internal factors caused by the school's HR qualifications are not in accordance with the scientific competencies charged; external factors in the form of lack of attention of parents in supervising and directing their children and the busyness of parents at work which has an impact on the lack of attention to children.